2007
DOI: 10.1051/0004-6361:20078210
|View full text |Cite
|
Sign up to set email alerts
|

H-atom bombardment of CO2, HCOOH, and CH3CHO containing ices

Abstract: Context. Hydrogenation reactions are expected to be among the most important surface reactions on interstellar ices. However, solid state astrochemical laboratory data on reactions of H-atoms with common interstellar ice constituents are largely lacking. Aims. The goal of our laboratory work is to determine whether and how carbon dioxide (CO 2 ), formic acid (HCOOH) and acetaldehyde (CH 3 CHO) react with H-atoms in the solid state at low temperatures and to derive reaction rates and production yields. Methods.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 41 publications
(102 reference statements)
3
89
1
Order By: Relevance
“…Experimental studies show that dissociative reactions may be the favored outcome of hydrogenating larger molecules and fragments (e.g. Bisschop et al 2007a), hampering the build-up of large quantities of complex molecules. Quantitative experiments are, however, still lacking for most reactions.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Experimental studies show that dissociative reactions may be the favored outcome of hydrogenating larger molecules and fragments (e.g. Bisschop et al 2007a), hampering the build-up of large quantities of complex molecules. Quantitative experiments are, however, still lacking for most reactions.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%
“…Astronomical observations, detailed laboratory studies, and progress in UHV surface techniques allow experimental verification of the initial surface reaction schemes, as introduced by Tielens, Hagen, and Charnley (Tielens & Hagen 1982;Tielens & Charnley 1997). Recently the formation of water was demonstrated in hydrogenation schemes starting from solid molecular oxygen (Miyauchi et al 2008;Ioppolo et al 2008) and the formation of ethanol from acetaldehyde (Bisschop et al 2007a). The first solid-state astrochemical laboratory studies focused on the formation of formaldehyde and methanol by H-atom bombardment of CO ice.…”
Section: Introductionmentioning
confidence: 99%
“…Although non-energetic surface reaction pathways leading to the formation of the more complex species studied in this work have not yet been investigated in the laboratory, several models indicate that those species should be formed in the solid phase and could participate in the formation of even more complex species. 11 For instance, Bisschop et al 52 studied the surface hydrogenation of acetaldehyde and found that it converts to ethanol (C 2 H 5 OH) or to CH 4 , H 2 CO, and CH 3 OH.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%